2021
DOI: 10.1371/journal.pone.0260327
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-21-3p associates with breast cancer patient survival and targets genes in tumor suppressive pathways

Abstract: Breast cancer is the cancer most often diagnosed in women. MicroRNAs (MIRs) are short RNA molecules that bind mRNA resulting in their downregulation. MIR21 has been shown to be an oncomiR in most cancer types, including breast cancer. Most of the effects of miR-21 have been attributed to hsa-miR-21-5p that is transcribed from the leading strand of MIR21, but hsa-miR-21-3p (miR-21-3p), transcribed from the lagging strand, is much less studied. The aim of the study is to analyze whether expression of miR-21-3p i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 74 publications
5
21
0
Order By: Relevance
“…Examination of miRNAs for specific fractions can significantly increase both the sensitivity and specificity of selected circulating miRNAs as noninvasive biomarkers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…Examination of miRNAs for specific fractions can significantly increase both the sensitivity and specificity of selected circulating miRNAs as noninvasive biomarkers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…The 14 miRNAs were correlated with the prognosis of patients with carcinoma of colon. However, other researchers have reported that upregulation of hsa-miR-194-3p was associated with the early T-stages [41].Studies have shown that high levels of mir-21-3p are associated with short survival time, poor prognosis, pathological features and positive lymph nodes [42]. Its overexpression in breast tumors is a sign of disease deterioration.…”
Section: Discussionmentioning
confidence: 96%
“…However, other researchers have reported that upregulation of hsa-miR-194-3p was associated with the early T-stages [41]. Genes Hen G, etl found that hsa-miR-200c-5p was key regulator in HCV-HCC development by analyzing transcriptome-sequencing data [42,43]. Up-regulation of hsa-miR-221-3p affects proliferation and apoptosis of cells via Bcl-xL/Bax pathway.…”
Section: Figure 8 Discussionmentioning
confidence: 99%